Sex-specific association between coffee consumption and inflammation: the population-based Tromsø7 Study - Gjesvik, Emelia Emmanuella (UiT Norges arktiske universitet, 2024)
Abstract Introduction: Various studies have explored the association between coffee consumption and the risk of inflammation, yet results are inconsistent. Few studies have examined these association separately in women and men and by type of coffee consumed. We therefore aimed to further investigate this association in a heavy coffee drinking population by including four different methods of coffee brewing and exploring these associations separately for women and men using laboratory measured C-reactive protein (CRP) levels. Aim: The aim of this study is to examine the association between coffee consumption and inflammation in women and men in the seventh survey of the Tromsø Study (Tromsø7). Methods and material: This is a cross-sectional study utilizing data from Tromsø7 (2015-2016). After exclusions, the final study sample consisted of 6411 women and 6232 men aged 40 to 100 years. Descriptive statistics were used to describe the study participants according to total coffee consumption, filtered coffee, boiled coffee, instant coffee, and espresso consumption. The differences between the different levels of coffee consumption were tested using Chi-square and ANOVA tests. Odds ratios (ORs) and confidence intervals (CIs) from multivariable binary logistic regression analyses were used to estimate the association between coffee consumption and inflammation. All analyses were performed separately for women and men. Results: Most women and men consumed high-moderate levels of coffee (3-5 cups per day). The most consumed coffee type was filtered coffee. In women, compared to zero consumers, low moderate, high moderate and heavy consumers had ORs and CIs of 0.73 (0.59-0.90), 0.57 (0.47-0.70), 0.59 (0.47-0.73) respectively. Consumption of filtered coffee, instant coffee, and espresso was associated with a lower risk of inflammation, but no association was found for boiled coffee consumption in women. No associations were found in men. Conclusion: Coffee consumption is associated with lower risk of inflammation in ...